Augmenting mindfulness training through neurofeedback: a pilot study of the pre-post changes on resting-state functional connectivity in typically developing adolescents - Cosgrove, Kelly T.; Tsuchiyagaito, Aki; Cohen, Zsofia P.; Cochran, Gabe; Yu, Xiaoqian; Misaki, Masaya; Aupperle, Robin L.; Singh, Manpreet K.; Paulus, Martin P.; Kirlic, Namik (Frontiers in Neuroscience, 2024)
BackgroundMindfulness training has been shown to promote positive mental health outcomes and related changes in neural networks such as the default mode network, which has a central node in the posterior cingulate cortex (PCC). Previous work from our group reported on the impact of a novel, neurofeedback augmented mindfulness training (NAMT) task on regulation of PCC hemodynamic activity in typically developing adolescents. The present pilot study aimed to expand on this finding by examining the pre-post changes of the NAMT task on resting-state functional connectivity of the PCC.MethodsThirty-one typically developing adolescents (14.77 ± 1.23 years; 45% female) underwent a resting-state functional magnetic resonance imaging scan both before and after completing the NAMT task. A linear mixed effects model was used to assess for changes in functional connectivity of the PCC across the two resting-state runs.ResultsData did not support the hypothesized decrease in connectivity between the PCC seed and other DMN regions from pre- to post-NAMT task. However, we observed a significant increase in functional connectivity between the PCC and a cluster encompassing the left hippocampus and amygdala following completion of the NAMT task (run 1 Fisher’s Z = 0.16; run 2 Fisher’s Z = 0.26).ConclusionAlthough preliminary, this finding suggests NAMT has the potential to strengthen connectivity between default mode and salience regions. We speculate that such changed connectivity may facilitate enhanced self-referential and emotional processing in adolescents.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT04053582.